Physiological properties of cold-sensitive suppressor mutations of a temperature-sensitive dnaZ mutant of Escherichia coli. - Blinkowa, A (1983)
Suppressors of a temperature-sensitive dnaZ polymerization mutant of Escherichia coli have been identified by selecting temperature-insensitive revertants. Those suppressed strains which concomitantly became cold sensitive were chosen for further study. Intragenic suppressor mutations, which caused cold-sensitive defects in DNA polymerization, were located in dnaZ by transduction with lambda dnaZ+ phages. Extragenic suppressor mutations were mapped within the initiation gene dnaA. These suppressor-containing strains were defective in initiation at low temperature as determined by measurements of DNA synthesis in vivo and in toluene-treated cells. The occurrence of suppressor mutations of dnaZ(Ts) within the dnaA gene is considered evidence that the dnaA and dnaZ products interact in vivo. A second indication of a dnaA-dnaZ protein-protein interaction was provided by the observation that the introduction of additional copies of the dnaZ+ gene into a strain carrying the dnaA suppressor mutation was lethal [whether the strain was dnaZ+ or dnaZ(Ts)].